Travel insurance for young travellers - Chua, Pei Pei (2014)
The World Tourism Organisation( WTO ) has estimated that out of every five international arrivals, one would be a youth. It is also reported that youth tourism is growing at a fast rate. It is, therefore, necessary that travel insurance packages available in the market cater to the needs of the youths. A survey of the insurance policies available at present brings out that these have not been designed to meet the needs of the youths. This necessitated a detailed study of the suitability of the available travel insurance packages.